(untitled) (Applied Biological Research, 2025)
Diabetes mellitus is an endocrine disorder caused by inadequate insulin or insulin resistance, leading to elevated blood glucose levels. This study aimed to evaluate the anti-diabetic potential of plant-based silver nanoparticles (AgNPs). AgNPs from drumstick (Moringa oleifera), okra (Abelmoschus esculentus), and periwinkle (Catharanthus roseus) were synthesized using a green synthesis approach. Characterization of the plant-based AgNPs was carried out using UV-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FESEM).UV-visible spectroscopy revealed surface plasmon resonance peaks at 400 nm for M. oleifera-AgNPs (MO-AgNPs) and 401 nm for both C. roseus-AgNPs (CR-AgNPs) and A. esculentus-AgNPs (AE-AgNPs). FTIR analysis identified various functional groups present in the AgNPs. FESEM images showed spherical nanoparticles sized 12–22 nm (AE-AgNPs), 21–46 nm (CR-AgNPs), and 13–49 nm (MO-AgNPs). Dynamic light scattering (DLS) analysis indicated maximum size distributions at 50 nm (CR-AgNPs), 70 nm (AE-AgNPs), and 40 nm (MO-AgNPs).The plant-based AgNPs exhibited significant anti-diabetic activity against carbohydrate-digesting enzymes such as amylase and glucosidase. All three synthesized AgNPs increased α-amylase and α-glucosidase enzyme inhibition. The D-glucose diffusion retardation index (GDRI) of AE-AgNPs and MO-AgNPs was comparable to the standard anti-diabetic drug, acarbose. Thus, these plant-based AgNPs demonstrate promising anti-diabetic potential and may be further explored for use in diabetes-related medicinal formulations.